Strategy of PT. XYZ Facing Expiry of Contract in 2025 and Change of Company Vision (The Indonesian Journal of Business Administration, 2021)
PT. XYZ is a subsidiary of PT. MNO and a sister company of PT. ABC. PT. XYZ has a contract of coal hauling, heavy equipment rental and road maintenance with PT. ABC. PT. ABC has a contract of coal mining with government until 2025. PT. XYZ also will be ended the contract by PT. ABC. Besides, old vision of PT. XYZ, “To Be A Leading Mining Company in Indonesia,” was changed to new vision, “To Be A National Supply Chain Management Company” as a recovery from bad performance of two business units that were ended by PT. ABC. PT. XYZ must set strategies to face end of PT. ABC’s contract with government in 2025 and change of company vision.To face end of PT. ABC’s contract with government in 2025, PT. XYZ must know estimated coal hauling target in 2021-2025. There are two allocation scenarios of the target because there are two contractors at same area (PT. XYZ and PT. DEF). First, 60% of the target for PT. XYZ and 40% for PT. DEF (PT. XYZ does not require investment to achieve the target). Second, 100% of the target for PT. XYZ (PT. XYZ requires investment to achieve the target). On the other hand, bad coal price condition reduces the target by 20%. Probability of good coal price condition is 60% and bad coal price condition is 40%. By using decision tree and NPV method, scenario of 100% of the target gives PT. XYZ higher NPV than scenario of 60% of the target but the decision will be matched with strategy to face change of company vision.To face change of company vision, by quantifying and combining analysis result of external and internal condition, PT. XYZ should use generic corporate strategy of diversification. It is matched with the new vision because general concept of the new vision is PT. XYZ must analyze any potential business (mining and non-mining) then PT. XYZ must use vendors/subcontractors to do the job. To position business in the market, PT. XYZ should use generic business strategy of cost leadership and non-equity alliance. To organize activities as support for business strategy more details, PT XYZ should use functional strategy that focuses on technology function, logistic and operation function, business development function and human resources function.By matching those two strategies, PT. XYZ should choose scenario of 60% of coal hauling target rather than 100% of the target. PT. XYZ should diversify current business become mining services by using applicable technology and supporting equipment rental services. PT. XYZ should do further market analysis for potential business diversification like supplier of stone, supplier of concrete product, civil contractor in mining activities, expedition vendor and fabrication activity. Keywords: decision tree, net present value, strategy management, corporate strategy, business strategy, function strategy.